Pengaruh Current Ratio, Return On Asset, Return On Equity, Debt To Equity Ratio, Total Turnover Asset, dan Dividend Policy Terhadap Harga Saham - Margaret Calista; Indra Widjaja (Universitas Tarumanagara, 2019)
This study aims to analyze factors that affect the stock price that are listed in BEI within a period between year 2012 to 2015. This research is a study to determine the influence between Current Ratio, Return on Asset, Return on Equity, Debt to Equity Ratio, Total Turnover Asset, and Dividend Policy towards stock price. The population used in this research are all manufacture companies that are listed in BEI during the research period. The samples are collected by using the purposive sampling method. This research used multiple linear regression, with t-statistic test, F-statistic test, and adjusted coefficient of determination to determine the truth about hypotheses. The result of this research are Return on Equity has significant effect on the stock price, while Current Ratio, Return on Asset, Debt to Equity Ratio, Total Turnover Asset, and Dividend Policy has non-significant effect on the stock price. Together, Current Ratio, Return on Asset, Return on Equity, Debt to Equity Ratio, Total Turnover Asset, and dividend policy have significant effect on stock price.